Radio interference analysis tool based on GNU Radio - Yébenes Gálvez, José Antonio; Martos-Naya, Eduardo; Aguayo-Torres, María del Carmen; Cárdenas-Angelat, Carlos; Baños-Polglase, Juana Daphne (My University, 2019)
Avoiding interference is one of the main challenges in radio communications. Interference hunting is usually done with costly instruments. In this work, a cost efficient portable tool is described for interference analysis that is based on software defined radio. A generic radio board implements the RF front end, while flexible signal processing is carried out on a personal computer. The proposed tool analyses spectrum characteristics spanning from 70 MHz to 6 GHz band, detects radio interference signals and helps to identify the type of radio technology used by the source transmitter.
Keywords: Radio; Interferencia eléctrica; GNU radio; Spectrum analyser; SDR; Energy detector; Interference